Changes of hepatic lipid mediators associated with intake of high-fat diet for 12 weeks in endotoxemic rats using LC-ESI-MS/MS. Issue 4 (August 2015) - Nishiokada, Aya; Miyoshi, Makoto; Fujiwara, Mayu; Aoyama-Ishikawa, Michiko; Maeshige, Noriaki; Takahashi, Michiko; Hamada, Yasuhiro; Usami, Yu; Honda, Mie; Arita, Makoto; Usami, Makoto
Summary Background & aims It has recently been reported that anti-inflammatory lipid mediators are increased in the late phase of acute inflammation, whereas proinflammatory lipid mediators are regulated at the initiation of inflammation. The purpose of this study was to evaluate changes of hepatic lipid mediators due to high-fat diet (HFD) feeding in endotoxemic rats. Methods Male Wistar rats were fed either HFD or control diet for 12 weeks, and were then killed 0, 1.5, and 6 h after lipopolysaccharide (LPS) injection. Analyses included lipidomics assessment of mediators using liquid chromatography-electrospray ionization/multi-stage mass spectrometry; measuring expression of hepatic polyunsaturated fatty acid (PUFA)-oxidizing enzyme, tumor necrosis factor (TNF)-α, interleukin (IL)-6, and inducible nitric oxide synthase mRNA levels; blood biochemical tests; and liver histology. Results HFD feeding worsened liver injury, increased expression of TNF-α and IL-6 mRNA, and increased oxidative stress after LPS injection. PUFA-oxidizing enzymes were higher in HFD-fed rats after LPS injection. The proinflammatory prostaglandin (PG)E2 and thromboxane B2 were increased 1.5 h after LPS injection, and had decreased by 6 h in HFD-fed rats. In contrast, potent pro-resolving resolvins derived from eicosapentaenoic acid and docosahexaenoic acid were not detected, but anti-inflammatory epoxyeicosatrienoic acids, lipoxin A4, and 15-deoxy-PGJ2 were increased after LPS injection in HFD-fed rats. Conclusions HFD feeding for 12 weeks enhanced proinflammatory lipid mediators 1.5 h after LPS injection suggesting relation to liver injury.